FUZZY BASED CONTROLLER FOR AC/DC BOOST CONVERTER - Radhi, Jawad; Ali, Dr. Ramzi S.; Fathel, Dr. Ali (Iraqi Journal for Electrical and Electronic Engineering, 2006)
In this paper, a fuzzy based controller for boost type AC/DC converter has been presented. Its operation and performance have been investigated through its simulation in the environment of Mat Lab. The system has been tested under various loading conditions. The obtained results showed that this fuzzy based controller can effectively control the power factor and the harmonic contents of the current drawn from the power factor system distribution network.